2005
DOI: 10.1007/s00267-004-4083-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Properties After Establishment of Artemisia halodendron and Caragana microphylla on Shifting Sand Dunes in Semiarid Horqin Sandy Land, Northern China

Abstract: In the semiarid Horqin sandy land of northern China, establishment of artificial sand-fixing shrubs on desertified sandy lands is an effective measure to control desertification and improve the regional environment. Caragana microphylla Lam. and Artemisia halodendron Turcz. ex Bess. are two of the dominant native shrub species, which are adapted well to windy and sandy environments, and thus, are widely used in revegetation programs to control desertification in Horqin region. To assess the effects of artifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
58
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 14 publications
5
58
1
Order By: Relevance
“…Laclau (2003) and found that because of the biomass accumulations, soil organic matter increases with the extension of the revegetation time, in semi-arid areas. The present results are consistent with the findings of Su and Zhao (2003), who reported higher SOC in stands of C. microphylla shrub than in active sand dunes. Wei et al (2010) compared the distribution of SOC and N in soils under canopies and in outer tree canopies in semi-arid areas and found that dry-climate, low-C soils had a potential for C sequestration after grassland to woodland conversion.…”
Section: Soil Organic C and N Concentrationsupporting
confidence: 83%
See 1 more Smart Citation
“…Laclau (2003) and found that because of the biomass accumulations, soil organic matter increases with the extension of the revegetation time, in semi-arid areas. The present results are consistent with the findings of Su and Zhao (2003), who reported higher SOC in stands of C. microphylla shrub than in active sand dunes. Wei et al (2010) compared the distribution of SOC and N in soils under canopies and in outer tree canopies in semi-arid areas and found that dry-climate, low-C soils had a potential for C sequestration after grassland to woodland conversion.…”
Section: Soil Organic C and N Concentrationsupporting
confidence: 83%
“…Zhou et al (2011) investigated the dynamics of soil C and N accumulation over 26 years under controlled grazing in a desert shrubland. Su et al (2005) found that, after planting the shrubs Caragana microphylla Lam. and Artemisia halodendron Turcz.…”
mentioning
confidence: 99%
“…Approximately 70 species have been recorded in China and most of them grow on hills and in gullies, thickets, plains and plateaux (Zhang, 2005). They are ecologically important because they serve as forage resources for wild animals and are preferred plants for use in reforestation against desertification and erosion (Fan et al, 2007;Su et al, 2005). Most of the rhizobia associated with Caragana belong to the genus Mesorhizobium (Chen et al, 1995; Guan et al, 2008;Lu et al, 2009;Yan et al, 2007) and two species, Mesorhizobium tianshanense and Mesorhizobium caraganae, have been described so far (Chen et al, 1995; Guan et al, 2008).…”
mentioning
confidence: 99%
“…The vegetation restoration of sand dunes is a major challenge for ecologists (Schade and Hobbie 2005, Su et al 2005, Zhang et al 2006. In Shapotou area of Tengger desert, more than 50 years of succession of artificial sand-binding vegetation and the regional restoration of eco-environment are the theoretical verification and successful example for the desertification reversion (Li 2005).…”
Section: Discussionmentioning
confidence: 99%